The creative cosmos beyond humans: a symphony of participatory design and visual artificial intelligence - Zhao, YangYang (Frontiers in Communication, 2024)
As artificial intelligence (AI) continues its pervasive presence in our daily lives, it is imperative to expand the boundaries of participatory design to aspects of visual communication beyond humans. This research explores the intriguing convergence of participatory design and AIenabled visual-based design as powerful methodologies to shape the ways we create new ideas (e.g. products/services). The specific research objectives are threefold: to unravel the nuanced dynamics in terms of perception inherent in the increasingly intertwined visual communication between humans and AI (e.g. sketch AI); to investigate how AI-enabled visual communication supports the participatory process with stakeholders; to explore their experiences in AI-enabled visual-based design for non-human subjects (e.g. animals, plants). Through a laboratory study of 18 experimental groups, we have found the critical setting for increased creative ideation performance in the AI-enabled visual-based design when (novice) designers engage AI as a partner rather than simply a tool, or collaboratively interact with stakeholders. As such, the engagement level of internal stakeholders is much higher than that of external stakeholders.